Socioeconomic Status, Religion and Health in India: An Examination of Chronic and Communicable Diseases. Issue 2 (2016) - Childers, Trenita B.; Chiou, Kevin
The literature on socioeconomic status and health suggests that those in higher positions have better health, and those in lower positions have worse health. There is little evidence of an SES gradient in non-industrialized countries, however, and it is uncertain whether the health gradient established in many Western countries would apply in developing countries. In this study, the authors examine patterns in health outcomes by caste and religion in India, a developing country. Results from a nationally representative sample, the Indian Human Development Survey, suggest that while high SES social groups report less communicable disease, they report a higher prevalence of chronic diseases than low SES groups. This study demonstrates the need to examine diseases of affluence among high SES groups in developing countries while also identifying the particular health concerns that are prevalent among low SES groups.